4‐(Pentafluorosulfanyl)benzenediazonium Tetrafluoroborate: A Versatile Launch Pad for the Synthesis of Aromatic SF5 Compounds via Cross Coupling, Azo Coupling, Homocoupling, Dediazoniation, and Click Chemistry. Issue 8 (8th January 2014) - Okazaki, Takao; Laali, Kenneth K.; Bunge, Scott D.; Adas, Sonya K.
Abstract: The reagent 4‐(pentafluorosulfanyl)benzenediazonium tetrafluoroborate (1 ) was synthesized and isolated as a stable salt for the first time; its application in a wide assortment of transformations was subsequently investigated. A series of novel SF5 ‐bearing alkenes, alkynes, and biaryl derivatives were synthesized by employing Heck–Matsuda, Sonogashira, and Suzuki coupling protocols. Dediazoniation with TMSX (X = Hal; N3 ; and CN) and NH4 SCN in [BMIM][BF4 ] as solvent furnished the corresponding p ‐SF5 –C6 H4 X derivatives. The azide derivative p ‐SF5 –C6 H4 N3 entered into click chemistry with phenylacetylenes to furnish the corresponding triazoles. The 4, 4′‐bis(pentafluorosulfanyl)biphenyl was synthesized by homo‐coupling using Pd(OAc)2 . The corresponding azo compounds were obtained through azo‐coupling with reactive aromatic nucleophiles (1, 3‐dimethoxybenzene, 1, 3, 5‐trimethoxybenzene, 1, 2, 4‐trimethoxybenzene, aniline and phenol). Fluorodediazoniation in [BMIM][PF6 ] and [BMIM][BF4 ] selectively furnished the fluoro derivative p ‐SF5 –C6 H4 F. Dediazoniation in [BMIM][NTf2 ] gave p ‐SF5 –C6 H4 OS(O)(CF3 )=NSO2 CF3 as the major and p ‐SF5 –C6 H4 ‐NTf2 as the minor products. Homolytic dediazoniation in MeCN/NaI gave the unsymmetrical biaryls p ‐SF5 –C6 H4 ‐Ar (ArH = mesitylene and p ‐xylene) along with p ‐SF5 –C6 H4 I. Analysis of the dediazoniation product mixtures indicated that dediazoniation of p ‐SF5 –C6 H4 N2 + BF4 – in low nucleophilicity, highly ionizing, solvents (TfOH, TFE, HFIP, TFAH) is mainly heterolytic, while in MeOH it is mainly homolytic. The isodesmic reaction p ‐SF5 –C6 H4 + + R‐C6 H5  → SF5 –C6 H5 + p ‐R‐C6 H4 + (with R = NO2, CF3, H) was gauged by DFT at various levels and by PCM. Abstract : The utility of 4‐(pentafluorosulfanyl)benzenediazonium tetrafluoroborate as a versatile building block for the synthesis of a host of aromatic SF5 compounds through the application of cross coupling, azo‐coupling, homocoupling, dediazoniation, and click chemistry has been demonstrated.